2005
DOI: 10.1073/pnas.0503656102
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the mouse inositol 1,3,4,5,6-pentakisphosphate 2-kinase gene, associated lethality, and tissue distribution of 2-kinase expression

Abstract: Many functions have been suggested for inositol 1,2,3,4,5,6-hexakisphosphate (InsP 6), including mRNA export, nonhomologous end-joining, endocytosis, and ion channel regulation. However, it remains to be demonstrated that InsP6 is necessary for in vivo survival. We previously isolated a cDNA encoding the mammalian inositol 1,3,4,5,6-pentakisphosphate (InsP 5) 2-kinase (2-kinase), the enzyme that converts InsP 5 to InsP6. We used the sequence to search the BayGenomics databases and identify an ES cell line (XA2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
66
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 16 publications
(19 reference statements)
3
66
0
Order By: Relevance
“…Soluble inositol phosphates were extracted according to the method previously described (27). Briefly, cells were lysed in 500 l of methanol and 0.5 N HCl mixture (methanol, 0.5 N HCl ϭ 2:1) and inositol phosphates were extracted with 335 l of chloroform.…”
Section: Methodsmentioning
confidence: 99%
“…Soluble inositol phosphates were extracted according to the method previously described (27). Briefly, cells were lysed in 500 l of methanol and 0.5 N HCl mixture (methanol, 0.5 N HCl ϭ 2:1) and inositol phosphates were extracted with 335 l of chloroform.…”
Section: Methodsmentioning
confidence: 99%
“…Yes. Recent studies of several IPKs have demonstrated their essential involvement in organism development and function (17,(36)(37)(38)(39)(40)(41). Given the highly orchestrated nature of these processes, it is reasonable to conclude that the production of an IP code that emerges from IP 3 is involved in the execution of these instructions.…”
Section: G Protein Activation Along With Expression Of the Four Evolmentioning
confidence: 99%
“…We did not use RNA interference to reduce expression of the InsP 5 kinase that synthesizes InsP 6 . This decision was based on previous experiments showing that "knockdown" of mammalian InsP 5 2-kinase expression induces gross changes in nuclear morphology (41), is pro-apoptotic (42), and generally toxic (43,44). Instead, we overexpressed MINPP, an InsP 6 phosphatase.…”
Section: The Effect Of Minpp Upon Insp 6 Levels and Nucleolinmentioning
confidence: 99%